ZIGZAGS OF THE JUDICIAL REFORM IN GEORGIA (Law and world, 2019)
I extend warm greetings to everybody – speakers, foreign guests and especially inspiring persons and initiators of the conference. Wish you the best of luck; I have no doubts with this regard considering the successful presentation of the program and the ﬂ ow of the procedure. Herewith, given that the conference is devoted to Topical issues of Justice, which primarily represents the current concern, I feel the need to have a very general outline of an early period of the reform, lack of which it might make difﬁcult to perceive, estimate and further transform the present circumstances. This is equally related to beneﬁcial and suitable, as well as, loss-making and hazardous salient factors.